003.2 The contribution of mycoplasma genitalium to the aetiology of sexually acquired proctitis in men who have sex with men. (13th September 2015) - Bissessor, M; Tabrizi, SN; Bradshaw, CS; Fairley, CK; Twin, J; Poljak, M; Peel, J; Hocking, JS; Garland, SM; Chen, MY
Abstract : Background: To determine the contribution of Mycoplasma genitalium to the aetiology of sexually acquired proctitis in HIV positive and HIV negative men who have sex with men (MSM). Methods: Consecutive MSM diagnosed clinically with proctitis between May 2012 and August 2013 were tested for: rectal M. genitalium by real time PCR assay; chlamydia by strand displacement assay; gonorrhoea by culture; and herpes simplex virus (HSV) by in-house PCR. M. genitalium load was determined by qPCR assay targeting the MgPa gene. The loads of rectal M. genitalium in men with symptomatic proctitis were compared to those in a control group of men (ratio 1:1) with rectal M. genitalium but no symptoms of proctitis. Results: Among 154 MSM with proctitis, rectal M. genitalium was detected in 12% (18/154, 95% CI: 6.9–17.1). Rectal M. genitalium was significantly more common among HIV positive men (10/48, 21%; 95% CI: 9.5–32.6) compared with HIV negative men (8/106, 8%; 95% CI: 2.9–13.1, p = 0.02). Among HIV positive men the rate of M. genitalium was comparable to that for chlamydia (21%), gonorrhoea (25%) and HSV (19%). The median load of M. genitalium among 18 men with symptomatic proctitis was significantly higher than the median load among 18 controls who had asymptomatic rectal M. genitalium (4.82 log10 load/sample versus 3.81 log10 load/sample, p = 0.016) Conclusion: M. genitalium was common among MSM with symptomatic proctitis, especially those with HIV. Comprehensive testing for multiple sexually acquired pathogens in MSM presenting with proctitis is required and should include testing for M. genitalium . Disclosure of interest statement: None to disclose.